Preservative solution for skeletal muscle biopsy samples - Yasemin Gulcan Kurt (Annals of Indian Academy of Neurology, 2015)
Context : Muscle biopsy samples must be frozen with liquid nitrogen immediately after excision and maintained at -80 o C until analysis. Because of this requirement for tissue processing, patients with neuromuscular diseases often have to travel to centers with on-site muscle pathology laboratories for muscle biopsy sample excision to ensure that samples are properly preserved. Aim: Here, we developed a preservative solution and examined its protectiveness on striated muscle tissues for a minimum of the length of time that would be required to reach a specific muscle pathology laboratory. Materials and Methods: A preservative solution called Kurt-Ozcan (KO) solution was prepared. Eight healthy Sprague-Dawley rats were sacrificed; striated muscle tissue samples were collected and divided into six different groups. Muscle tissue samples were separated into groups for morphological, enzyme histochemical, molecular, and biochemical analysis. Statistical method used: Chi-square and Kruskal Wallis tests. Results: Samples kept in the KO and University of Wisconsin (UW) solutions exhibited very good morphological scores at 3, 6, and 18 hours, but artificial changes were observed at 24 hours. Similar findings were observed for the evaluated enzyme activities. There were no differences between the control group and the samples kept in the KO or UW solution at 3, 6, and 18 hours for morphological, enzyme histochemical, and biochemical features. The messenger ribonucleic acid (mRNA) of β-actin gene was protected up to 6 hours in the KO and UW solutions. Conclusion: The KO solution protects the morphological, enzyme histochemical, and biochemical features of striated muscle tissue of healthy rats for 18 hours and preserves the mRNA for 6 hours.